Cuidado em território de exclusão social: covid-19 expõe marcas coloniais - Camilo, Claudia; Kahhale, Edna; Ferreira, Maria Luísa; Schveitzer, Mariana (Saúde e Sociedade, 2021)
A intersecção de gênero, raça e classe marca os territórios de exclusão social, especialmente em um país que carrega cicatrizes da colonialidade patriarcal e capitalista em suas estruturas, como é o caso do Brasil. O objetivo deste trabalho é compreender o cuidado em um desses territórios: a cidade de Cubatão/SP. A investigação, feita entre 2017 e 2020, incluiu a pandemia da covid-19, que sobrecarregou o cuidado no território. O método foi a pesquisa qualitativa, com oficinas, observação participante e entrevistas de profundidade. O cuidado era majoritariamente oferecido por mulheres, líderes comunitárias e profissionais da atenção primária do Sistema Único de Saúde. Para analisar os dados, utilizou-se a hermenêutica de profundidade. O referencial teórico foi a costura das teorias feministas da ética do cuidado, ecofeministas e interseccionais. A pesquisa revelou diversos desafios e potencialidades, como o cuidado ético-político, eixo da busca por justiça socioambiental. , Abstract The intersection of gender, race and class marks the territories of social exclusion, especially in a country that carries scars of a patriarchal and capitalist colonialism in its structures, as is the case in Brazil. The objective was to understand care in this territory of exclusion in Cubatão, São Paulo, Brazil. The research, conducted between 2017 and 2020, included the pandemic of COVID-19, which overloaded care in this territory. The method was qualitative research, with workshops, participant observation and in-depth interviews. The care delivered by community leaders and primary health care professionals from the Brazilian National Health System was mostly performed by women. For data analysis, depth hermeneutics was used. The theoretical reference was the perspective of feminists: ecofeminist, intersectional and Care Ethics. The study showed several challenges and the ethical-political care as an axis in the search for social and environmental justice.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; brésil; care; covid-19; intersectionnalité; pandémie; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; travail; écoféminisme

Genre, rap et enjeux de la visibilité dans l'espace public des rappeuses à Montréal - Lesacher, Claire (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Cet article, basé sur une enquête de terrain menée en 2011, à Montréal, porte sur les enjeux qui traversent la question de la présentation physique des rappeuses dans l’espace public. Au cours des entretiens, les rappeuses soulignent que les activités de médiatisation et de représentation sur scène impliquent de devoir composer avec des représentations situées de la féminité dans un contexte où les industries musicales et médiatiques favorisent leur visibilité d’abord en tant que femmes, ce qui a des effets sur leur reconnaissance/légitimité en tant qu’artiste. Cette étude jette un regard sur les processus qui s’organisent dans une activité rap majoritairement masculine, elle-même durablement évincée des espaces dominants de production et de médiatisation de la musique au Québec.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; chanson; corps; femmes* artistes; féminisme matérialiste; genre; intersectionnalité; montréal; périodes historiques; québec; rapports sociaux de sexe; représentations du corps; ressource en ligne; régions géographiques; thématiques; étude qualitative

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Sexual citizenship through resistance: a movement that centers disabled women’s voices - MacKeigan, Tanya (Disability & Society, 2021)
This research examines the discourses that shape disabled women’s sexual subjectivity. I wanted to see how disabled women’s understanding of themselves as sexual is socially influenced. I held a focus group and individually interviewed five self-identified physically disabled women about their sexual lives. They shared detailed stories of personal experiences and societal influences. The main social influences that were present in the women’s stories were ableism, sexism, and resistance; the focus of this article is resistance. Resistance discourses challenge mainstream notions of disability and sexuality and combat the oppression that ableism and sexism can create. It is important work to highlight these resistance narratives; they are often overlooked in society. Diverse social understandings of disability and sexuality are needed, and it is important that they come from disabled people. This research seeks to make space for disabled perspectives in the interest of sexual inclusivity and sexual citizenship for disabled women.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; EDI; accessibilité; amériques; approches et analyses; canada; capacitisme; care; colombie-britannique; corps; cours; discipline; droit des personnes en situation de handicap; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex1911; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Altérité et création : comment peut-on s'épanouir artistiquement dans la différence, au-delà des discours sur la diversité ? - Symon, Henri (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Comment le fait d’être métis égypto-québécois·e influe-t-il sur ma manière de composer, d’écrire, de dessiner ? Et le fait d’être queer, neurodivergent·e, pauvre, ou encore d’avoir souffert de troubles de santé mentale ? Autrement formulé : comment, à partir d’une posture intersectionnelle, peut-on s’inscrire dans un cadre artistique donné et communiquer nos codes à un public qui ne les possède majoritairement pas ? Comment parler de ma voix propre, particulièrement minoritaire, afin d’éviter que d’autres s’approprient ma réalité ? Voilà les questions principales qui sont abordés dans cet article où je présente mon travail où partitions graphiques, poésie et arts visuels ont constitué le socle de ma démarche artistique au fil de plus d’une décennie de création. Pour y répondre, j’aborderai certains concepts-clés (intersectionnalité, tiers-espace, etc.) centraux dans ma réflexion, deux projets qui adressent de front ces questions et réalités, et, surtout, de nombreuses digressions proposant des bribes d’imaginaires les sous-tendant. Les projets abordés sont d’abord mon premier opéra, Le Désert mauve, d’après un texte éponyme de Nicole Brossard — chef-d’oeuvre des littératures lesbiennes, queers et québécoises. Puis le spectacle L’Outre-rêve et plus spécifiquement ma pièce L’amour des oiseaux moches, commande de l’Ensemble contemporain de Montréal (ECM+), où mes mots, ma musique et mes visuels donnent vie à quatre personnages imbus de réalisme magique (Djinn, Louve, Vieux Clown et Eunuque que j’aime) par l’entremise de pièces pour voix, scie musicale, accordéon et orchestre.
Keywords: 2000 à aujourd'hui; 2010-2019; DIG; LGBTQIA2+; amériques; approches et analyses; arts; discipline; identités LGBTQIA2+; intersectionnalité; invisibilisation; musique; neurodivergence; point de vue situé; privilèges; périodes historiques; queer; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques

Informal caregiving and strains: Exploring the impacts of gender, race, and income - Willert, Bria; Minnotte, Krysta Lynn (Applied Research in Quality of Life, 2021)
Informal caregivers are those who provide care for others without compensation. In the US, 85 % of elderly individuals receive care from an informal caregiver, and this number is expected to increase. Caregivers often experience different types of strain, stemming from physical, emotional, and financial demands. Guided by intersectionality theory, this study explores the relationships between informal caregiving strains and gender, race, and income, along with various control variables, including age, marital status, education, number of hours spent providing care, and employment status. Data from the 2015 Caregiving in the US survey (N = 1248) were used. Findings indicated male informal caregivers reported more financial strain compared to females. White women reported more emotional strain than women of color, and those with higher incomes reported less financial strain. Gender, race, and income were not significantly related to physical strain among informal caregivers. Implications, limitations, and suggestions for future research are discussed. © 2019, The International Society for Quality-of-Life Studies (ISQOLS) and Springer Nature B.V.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; care; détresse psychologique; intersectionnalité; proche aidance; projet charge mentale; périodes historiques; régions géographiques; soins aux; stress financier; thématiques; états-unis

Guérison Collective Healing - Yuen, Felice; Gabriel, Wanda; Fast, Elizabeth (Guérison Collective Healing, 2021)
Aborder les expériences des femmes autochtones dans les prisons provinciales du Québec Vers une guérison collective Addressing the experiences of Indigenous women in Quebec’s provincial prison Towards Collective Healing
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; canada; communauté; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; militance; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système carcéral; système colonial; systèmes d'oppressions; thématiques; travail social; violences